Concentric and Eccentric Target MRI Signs in a Case of HIV-Associated Cerebral Toxoplasmosis - Adam D. Roche; Dominic Rowley; Francesca M. Brett; Seamus Looby (Case Reports in Neurological Medicine)
Cerebral toxoplasmosis is one of the most common causes of focal brain lesions in immunocompromised patients, such as those with human immunodeficiency virus (HIV). Differentiating toxoplasmosis from other central nervous system (CNS) lesions provides a significant clinical challenge. Magnetic resonance (MR) imaging of the brain is key to prompt diagnosis and treatment of cerebral toxoplasmosis. Several specific signs on MRI of brain have been described in recent literature including the “concentric target sign” and “eccentric target sign.” We report a case of successfully treated HIV-associated cerebral toxoplasmosis in which both MRI signs were present simultaneously.